Immersive multimodal interactive presence - Giachritsis, Christos D.; Peer, Angelika (Springer series on touch and haptic systems, 2012)
Immersive Multimodal Interactive Presence presents advanced interdisciplinary approaches that connect psychophysical and behavioral haptics research with advances in haptic technology and haptic rendering.   It delivers a summary of the results achieved in the IMMERSENCE European project and includes selected chapters by international researchers. Organized into two parts: I. Psychophysical and Behavioral Basis and II. Technology and Rendering, it is an excellent example of interdisciplinary research directed towards the advancement of multimodal immersive virtual environments with particular focus on haptic interaction.   The twelve chapters of the book are grouped around three different scenarios representing different types of interactions in virtual environments: Person-Object (PO), Person-Object-Person (POP) and Person-Person (PP) interaction. Recent results of psychophysical and behavioral studies are reported along with new technological developments for haptic displays and novel haptic rendering techniques.